1985
DOI: 10.1136/bmj.291.6494.501
|View full text |Cite
|
Sign up to set email alerts
|

Impaired phagocytic activity of neutrophils in patients receiving haemodialysis: the critical role of iron overload.

Abstract: The metabolic burst (as measured by the spontaneous and stimulated nitroblue tetrazolium tests), the phagocytosis of heat inactivated bakers' yeast and of Staphylococcus aureus, the killing of Staph aureus, and the myeloperoxidase activity of polymorphonuclear neutrophils were studied in 11 patients receiving maintenance haemodialysis. Of these patients, six were polytransfused and had high serum ferritin concentrations (mean 5940 (SD 2925) [tg/l; group 1), and five had normal serum ferritin values (mean 171 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 19 publications
2
49
1
Order By: Relevance
“…Human polymorphonuclear granulocytes (PMNs) were harvested and purified as previously reported (23). In order to study the effect of PMNs on spore germination, spores were washed in HBSS and incubated in 10% normal human pooled serum during 10 min at 370C, washed in HBSS and diluted to 1,000/Ml.…”
Section: Methodsmentioning
confidence: 99%
“…Human polymorphonuclear granulocytes (PMNs) were harvested and purified as previously reported (23). In order to study the effect of PMNs on spore germination, spores were washed in HBSS and incubated in 10% normal human pooled serum during 10 min at 370C, washed in HBSS and diluted to 1,000/Ml.…”
Section: Methodsmentioning
confidence: 99%
“…There are several reasons for this so-called "iron apprehension": (i) A clinical trial that was performed almost three decades ago in 137 Fe-deficient individuals in Somalia showed that the risk for infection in those who received Fe supplementation was almost five times higher than those who received placebo (63); (ii) in the pre-ESA era, there have been frequent reports about the risk and consequences of Fe overload as a result of blood transfusion or Fe administration to anemic dialysis patients (64,65); (iii) several in vitro studies have indicated the association between Fe supplementation and oxidative stress in cell cultures (66,67); and (iv) a limited number of observational studies have indicated an association between high serum ferritin and infection (65,68) or mortality (52) and between Fe administration and indices of cardiovascular disease (69) or death risk (70) in dialysis patients.…”
Section: The "Iron Apprehension"mentioning
confidence: 99%
“…Another main cause for increased susceptibility to infections in patients with iron load are abnormalities of PM N function [18,24], Waterlot et al [25] described an inverse correlation between ferritin content and index of PMN yeast phagocytosis in hemodial ysis patients. Tielemans et al [26] and Tielemans and Lenclud [27] found increased bacterial infections and septicemia in hemodialysis patients with ferritin levels above 500 pgl/I.…”
mentioning
confidence: 99%